Rummet mellem kønnene - Rösing, Lilian Munk (Kvinder, Køn & Forskning, 1999)
What is the space between the sexes? Patriarchal theories has (directly and indirectly) defined this space as Phallus, the Other, Nothing, The Child, or even Woman herself. I try to examine these definitions critically while giving my own answer: The space between the sexes is the space that constitutes gender as a kind of phenomenological gender, beyond the dichotomy of "sex" and "gender". That is, gender is the outline between man and woman that defines man and woman respectively; gender (as an existential categoy) is something that happens in the meeting between man and woman, if we are able to see the other as different as well as similar. The essay is very much inspired by the sexual ethics of Luce Irigaray.